Legal Protection On Consumers Of Fintech Peer To Peer Lending Due To Covid-19 Pandemic - Debora Debora (Faculty of Law, Andalas University, 2021)
In March 2020, the WHO stated Covid-19 is pandemic disease. The Indonesian government has taken actions to prevent the spreading of Covid-19 by limiting people’s activities. Covid 19 has resulted in people who loans at lending institutions, having difficulty paying installments. The government issues policies in response to the Covid-19 effect, such as economic relaxation. However, the policy did not cover consumers Fintech Peer to Peer (P2P) Lending, this created a legal vacumm. The problem in this research is the urgency of legal protection for Fintech P2P lending consumers during pandemic Covid-19. The purpose of this research is for OJK policy to issue a stimulus to Fintech P2P Lending consumers. This research applied juridicial normative methodology. It uses secondary data, which consists primary legal material, namely the OJK regulations on Covid-19 prevention and related literature, analyzed descriptively analytically. The research shows that consumer fintech P2P lending are affected by Covid-19 pandemic, so they need to get legal protection, in the form of stimulus given to lenders and borrower of fintech P2P lending.